(untitled) (American Journal of Medical Science and Innovation, 2023)
Hepatitis B virus (HBV) is a common blood borne infectious agents causing high morbidity and mortality that constitute the major global health problems. Infection with HBV results in a wide spectrum disease from subclinical to fulminant hepatitis leading to death. The most important laboratory screening test for the diagnosis of early HBV is the immunoassay for HBsAg. Different analytical methods are being used now a days for the diagnosis of hepatitis namely, ICT, ELISA, CMIA and PCR. The aim of the study to determine viral hepatitis (HBV) seromarkers in suspected patients using different methods ICT and ELISA. This cross sectional study was conducted at the Immunology laboratory, BIHS General Hospital, Dhaka. A total 240 of HBsAg test results of the patients were collected from Laboratory register book. All tests were carried out by ELISA & ICT methods and compare between them. Majority (76.3%) of the donors was within the age group of 19-30 years. Among the donors, male donors were predominant (93.75%) than female (6.25%). A total number of 240 HBsAg tests were done in ICT method and found 6 Positive (2.5%) of them. Then we done correspondence test to confirm these by ELISA method and found 100% negative results. This study shows ICT method were able to determine HBsAg negative samples reasonably well that was detected negative by ELISA. ELISA method is more specific and sensitive than that of ICT.